1) (x+2)*4=2*4+2*4
(x+2)*4=(2+2)*4
x+2=4*4:4
x=4-2
x=2
Для x=2.
2) (5-3)*x=5*x-3*x
2*x=2*x
2*x-2*x=0
0=0
Для любых x!
3) (5-3)*x=5*x-3*2
2*x=5*x-6
5*x-2*x=6
3*x=6
x=6:3
Пошаговое объяснение:
1.4x+8=8+8
4x=8
2. 5x-3x=5x-3x
2x=2x (верно) , значит x∈(-∞;+∞)
3.5x-3x=5x-6
2x=5x-6
2x-5x=-6
-3x=-6
1) (x+2)*4=2*4+2*4
(x+2)*4=(2+2)*4
x+2=4*4:4
x=4-2
x=2
Для x=2.
2) (5-3)*x=5*x-3*x
2*x=2*x
2*x-2*x=0
0=0
Для любых x!
3) (5-3)*x=5*x-3*2
2*x=5*x-6
5*x-2*x=6
3*x=6
x=6:3
x=2
Для x=2.
Пошаговое объяснение:
1.4x+8=8+8
4x=8
x=2
2. 5x-3x=5x-3x
2x=2x (верно) , значит x∈(-∞;+∞)
3.5x-3x=5x-6
2x=5x-6
2x-5x=-6
-3x=-6
x=2